Impikasi Modal Manusia dan Ekonomi Digital terhadap Penyerapan Tenaga Kerja Sektor Formal di Nusa Tenggara Barat pada Masa Pandemi Covid-19 - Erwin Zindana Wazari; Karina Dwi Agustiarini (Seminar Nasional Official Statistics, 2022)
Decent work is a major aspect in efforts to reduce poverty and succeed in sustainable development, which is stated in the 8th goal of the SDGs. Employment problems are one of the problems that must be considered by the government where the condition of the labor force increases every year but is not matched by the availability of decent jobs. In West Nusa Tenggara Province, the availability of decent work is still relatively low. This can be seen through the value of the Decent Work Indexin West Nusa Tenggara which is one of the lowest in Indonesia. This study aims to analyze the absorption of labor in the formal sector by taking into account human capital and the digital economy. The analytical methods used in this study include descriptive analysis with tables/graphs and inferential analysis with binary logistic regression. The results obtained from this study indicate that all independent variables have a significant partially effect on employment in the formal sector except for the variables of health complaints and marital status. Keywords: